Granulites and garnet–cordierite gneisses from Dronning Maud Land, Antarctica - Bucher-Nurminen, Kurt; Ohta, Yoshihide (Journal of Metamorphic Geology, 1993)
The central sector of Mühlig-Hofmannfjellet (3°E/71°S) in western Dronning Maud Land (East Antarctic shield) is dominated by large intrusive bodies of predominantly orthopyroxene-bearing quartz syenites (charnockites). Metasedimentary rocks are rare; however, two distinct areas with banded gneiss–marble–quartzite sequences of sedimentary origin were found during the Norwegian Antarctic Research Expedition NARE 1989/90. Cordierite-bearing metapelitic gneisses from two different localities contain the characteristic mineral assemblage: cordierite + garnet + biotite + K-feldspar + plagioclase + quartz ± sillimanite ± spinel. Thermobarometry indicates equilibration conditions of about 650°C and 4 kbar. Associated orthopyroxene–garnet granulites, on the other hand, revealed pressures of about 8 kbar and temperatures of 750°C. The earlier granulite facies metamorphism is not well preserved in the cordierite gneisses as a result of excess K-feldspar combined with interaction with an H2O-rich fluid phase, probably released by the cooling intrusives. These two features allowed the original high-grade K-feldspar + garnet assemblages to recrystallize as cordierite–biotite–sillimanite gneisses, completely re-equilibrating them. Phase relationships indicate that the younger metamorphic event occurred in the presence of a fluid phase that varied in composition between the lithologies.
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geologi

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Pages: Blad/Sheet 1 Publication Title: Norsk Polarinstitutt Temakart Nr. 24 Place: Oslo
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi